You don't have to go to church to be a good Christian: the implicit religion of the cathedral carol service congregation - Walker, David (Mental health, religion & culture, 2013)
The notion that you don't have to go to church to be a good Christian is accepted as an indicator of the form of implicit religiosity espoused by those who (in Bailey's analysis) say that they "believe in Christianity." The present paper builds on the findings of a recently published survey of rural Anglican churchgoers celebrating harvest which suggested that de-institutionalised implicit religion may be superseding commitment to conventional explicit religious attendance. The responses of 1081 people who attended Christmas carol services in two English cathedrals in 2009 and 2010 are analysed. The findings of the previous paper that implicit religiosity is more prevalent among younger people and among those who attend church less frequently are replicated. Evidence is also found that women are more inclined to this view than men and that those who have a loose historical connection through baptism are more likely to endorse it than those with either no historical connections or stronger ones. Suggestions are made for further research.